Upaya Fintech Syariah Mendorong Akselerasi Pertumbuhan UMKM di Indonesia - Saripudin Saripudin; Prameswara Samofa Nadya; Muhammad Iqbal (ITB AAS INDONESIA Surakarta, 2021)
Compared to other Islamic financial institutions, Islamic Fintech has some advantages in accelerating the growth of SME Enterprises in Indonesia. Nevertheless, the existence of Islamic Fintech is not free from various problems, such as regulation aspect, human resources aspect, also perception of society and potential fraud. This research sought to find solution of the problems with SWOT analysis, then comparing the aspects each other to find out strategies in the effort of growing Islamic fintech for accelerating SME Enterprises. The results are some strategies consisting of, first, ecosystem strengthening between Islamic Fintech, government, academics and civil society, including Islamic Fintech customers and Islamic Banks. Second, optimalization potential of Islamic Fintech in managerial skills also Islamic contracts capacity. Last, massive and targeted socialization and promotion of Islamic Fintech.